GE_GERICHTE C/5120/2012 vom 18. Oktober 2013 - GE Cour de justice (2013)
; ACTION DEVANT LE TRIBUNAL FÉDÉRAL ; RETOUR ; FRAIS JUDICIAIRES ; DÉPENS | CPC.106; LaCC.19; LaCC.20; LaCC.21; LaCC.22; LaCC.23; CPC.95; CPC.96; RTFMC.31